The Role of Innovation Strategy in Educating the Effect of Organizational Culture on Organizational Performance in SME’S of Silver Crafts in Gianyar District - Ni Putu Nila Evayanti Nila Evayanti; Putu Ngurah Suyatna Yasa; Ni Made Wahyuni (JUSTBEST: Journal of Sustainable Business and Management, 2022)
The industries of silver craft in Bali are centrally in the Celuk village. Results crafting gold and silver were produced in Celuk village have a quality high and can be produced in a large number. This research aims to how innovation strategies mediate the influence of organizational culture on the performance of silver handicraft SME’s organizations in Gianyar Regency especially Celuk village. The respondent of this research were 48 managers of silver handicraft enterpreneurs in Celuk village. The data is collect by interviews deployment questionnaire method. The data is analys using analysis descriptive and analytical inferential technique. Hypothesis test is using the Partial Least Square (PLS) analysis technique. The results are that organizational culture has a positive and not significant effect on organizational performance. Organizational culture has a significant positive effect on innovation strategies. It is showing the application of cultural organizations is quite strong against the performance of a company. The innovation strategy has a positive and significant effect on organizational performance and the innovation strategy is a full mediation between organizational culture and organizational performance. Innovation strategy is able to explain the relationship between organizational culture and organizational performance because the direct relationship between innovation strategy and organizational performance has a high relationship organizational culture with the concept of national culture.